Pencak Silat Profil Komposisi Tubuh dan Daya Tahan Kardiorespirasi Atlet Pencak Silat Pelatda Jawa Barat: Profil Komposisi Tubuh dan Daya Tahan Kardiorespirasi Atlet Pencak Silat Pelatda Jawa Barat - Ariya, Ariya Muharamsyah; Haqiyah, Aridhotul (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2024)
This research is motivated by the unknown profile of body composition and cardiorespiratory endurance of West Java pencak silat athletes. This research is a descriptive research on the level of physical fitness. The purpose of this study was to determine the profile of body composition and cardiorespiratory endurance profiles of West Java regional martial arts athletes. This type of research is descriptive research that aims to determine the profile of body composition and cardiorespiratory endurance of West Java regional pencak silat athletes. The method used in this research is survey. The test instrument uses BIA scales which will measure BMI, visceral fat, body fat and skeletal muscel and endurance tests using the bleep test instrument. The population in this study were West Java regional pencak silat athletes and used total sampling, namely 9 male athletes and 9 female athletes. The technique used in analyzing research data is to use descriptive statistics with descriptive analysis method of percentage analysis. From the results of the study the authors obtained the results of body fat there are 17% of athletes have high body fat and there are 83% of athletes have normal body fat with an average value of 19.6, visceral fat 11% of athletes have high visceral fat and there are 89% of athletes have normal visceral fat with an average value of 5.0, BMI there are 17% of athletes have excessive BMI and there are 83% of athletes have normal BMI with an average BMI of 22.7. Skeletal muscle there are 17% of athletes have high skeletal muscle and there are 83% of athletes have normal skeletal muscle with an average value of 32.2. Vo2Max there are 100% of athletes have high Vo2Max with an average value of 52.4. It can be concluded that the body composition and cardiorespiratory endurance of West Java regional pencak silat athletes are very good and ideal It is important for athletes and coaches to maintain ideal physical condition in order to get maximum results.